Pseudoginsenoside-F11 improves long-term neurological function and promotes neurogenesis after transient cerebral ischemia in mice. (February 2020) - Yuan, Linlin; Sun, Shibo; Pan, Xiaohan; Zheng, Liqin; Li, Yuting; Yang, Jingyu; Wu, Chunfu
Abstract: Stroke is the leading cause of long-term motor disability and cognitive impairment beside the acute brain injury. Recently, neurogenesis has become an attractive strategy for the chronic recovery of stroke. Our previous study showed that pseudoginsenoside-F11 (PF11), an ocotillol-type saponin, isolated from leaves of Panax pseudoginseng subsp., exerted neuroprotective effects on stroke by alleviating autophagy/lysosomal defects and repressing calcium overload. The present study investigated whether PF11 improved long-term functional recovery and promoted neurogenesis after ischemic stroke induced by transient middle cerebral artery occlusion (tMCAO) in mice. The data showed that PF11 (16, 32 mg/kg, p.o.) administrated once daily one week before tMCAO significantly reduced brain infarction and brain edema on day 3 after tMCAO. Also, PF11 attenuated the mortality, sensorimotor dysfunction, cognitive impairment and hippocampal atrophy of stroke mice. Moreover, the migration of neuroblasts and the generation of newborn neurons in ipsilateral striatum and dentate gyrus (DG) were significantly enhanced by PF11. In line with this, PF11 prevented the decreased survival rate of newborn neurons on day 42 after tMCAO. In addition, PF11 promoted proliferation and differentiation of neural stem cells in vitro. Furthermore, PF11's pro-neurogenic effect was attributed to its activation of the BDNF/TrkB, which was evidenced by that the pharmacological effects of PF11 was abolished by ANA-12, a specific inhibitor of BDNF receptor. Thus, the present study showed that PF11 could improve long-term neurological impairment and promote neurogenesis after stroke possibly through activating BDNF/TrkB pathway, indicating its potential role on treating ischemic stroke, especially chronic recovery. Highlights: PF11 (16, 32 mg/kg) improved sensorimotor dysfunction and cognitive impairment induced by transient cerebral ischemia. PF11 (16 mg/kg) enhanced neurogenesis in injured hippocampus and striatum of mice with transient cerebral ischemia. BDNF/TrkB pathway might be involved in the protective role of PF11 on transient ischemic stroke.